A Second Breeding Site for Ross's Gull (Rhodostethia rosea) in Nunavut, Canada - Béchet, Arnaud; Martin, Jean-Louis; Meister, Peter; Rabouam, Corinne (ARCTIC, 2000)
Only 15 cases of breeding of Ross's gull Rhodostethia rosea are known outside of Siberia. While numerous birds are regularly seen in the fall at Point Barrow, Alaska, until now only one breeding locality has been known for Nunavut, Canada. We found a second breeding locality in Nunavut in the northwestern corner of Prince Charles Island (Foxe Basin). We observed one pair incubating two eggs on a small island (30 m in diameter) situated in a medium-sized lake, on a low plateau at the top of a complex of raised beaches. None of the reports on aerial or land surveys of this region have mentioned the reproduction of this species, though unpublished aerial observations suggest that the species has been present during the 1980s. Outside Siberia, this species seems to be characterized by an irregular and scattered distribution of its breeding sites. Seuls 15 cas de reproduction de la mouette de Ross Rhodostethia rosea ont été rapportés en dehors de la Sibérie. Alors que de nombreux oiseaux sont observés à l'automne lors de leur passage à Point Barrow (Alaska), la reproduction au Nunavut (Canada) n'a été mentionnée qu'une seule fois. Nous documentons un deuxième site de reproduction pour le Nunavut, dans la partie nord-ouest de l'île du Prince-Charles (bassin Foxe). Un couple a été observé incubant deux œufs sur une petite île (environ 30 m de diamètre) située au milieu d'un lac de taille moyenne, sur un plateau bas constituant le sommet d'un complexe de plages surélevées. Aucun des rapports des levés aériens ou terrestres de cette région ne mentionne la reproduction de cette espèce, bien que des observations aériennes non publiées suggèrent sa présence au cours des années 80. En dehors de la Sibérie, cette espèce semble se caractériser par une distribution irrégulière et éparse des sites de reproduction.